Case report: Severe rhabdomyolysis and acute liver injury in a high-altitude mountain climber - Yun-Chih Yeh; Chien-Chou Chen; Chien-Chou Chen; Shih-Hua Lin (Frontiers in Medicine, 2022)
Concurrent severe rhabdomyolysis and acute liver damage are rarely reported in the setting of acute high-altitude illness (AHAI). We described a 53-year-old healthy mountain climber who experienced headache and dyspnea at the summit of Snow Mountain (Xueshan; 3,886 m above sea level) and presented to the emergency room with generalized malaise, diffuse muscle pain, and tea-colored urine. His consciousness was alert, and he had a blood pressure of 114/74 mmHg, heart rate of 66/min, and body temperature of 36.8°C. Myalgia of the bilateral lower limbs, diminished skin turgor, dry oral mucosa, and tea-colored urine were notable. Urinalysis showed positive occult blood without red blood cells. The most striking blood laboratory data included creatine kinase (CK) 33,765 IU/L, inappropriately high aspartate aminotransferase (AST) 2,882 IU/L and alanine aminotransferase (ALT) 2,259 IU/L (CK/AST ratio 11.7, CK/ALT ratio 14.9), creatinine 1.5 mg/dl, serum urea nitrogen (BUN) 26 mg/dl, total bilirubin 1.7 mg/dl, ammonia 147 μg/ml, lactate 2.5 mmol/L, and prothrombin time 17.8 s. The meticulous search for the underlying causes of acute liver injury was non-revealing. With volume repletion, mannitol use, and urine alkalization coupled with avoidance of nephrotoxic and hepatotoxic agents, his clinical features and laboratory abnormality completely resolved in 3 weeks. Despite rarity, severe rhabdomyolysis and/oracute liver injury as a potential life-threatening condition requiring urgent management may occur in high-altitude hypobaric hypoxia.